2011
DOI: 10.1002/jmv.22215
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of norovirus strains in Australian children from 2006 to 2008: Prevalence of recombinant strains

Abstract: Noroviruses are highly infectious and are the most common cause of gastroenteritis outbreaks. Genotype II.4 strains have been the dominant type identified in adults, however the genotype distribution in children is less clearly defined. This study aimed to detect and genotype norovirus strains infecting children hospitalized with acute gastroenteritis in Melbourne, Australia from 2006 to 2008. Stool samples were collected from 272 children admitted to the Royal Children's Hospital, Melbourne, Australia, with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
18
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 47 publications
5
18
0
Order By: Relevance
“…A single study conducted in the United States on norovirus strains collected in the 1970s showed that norovirus strains possessing a GII.3 VP1 gene and ancestral RdRp gene were the most prevalent genotype circulating in children at that time (22). Genotype GII.3/GII.3 (capsid/RdRp) noroviruses were prevalent in children globally from the late 1980s to the late 1990s (22,23,26,27) before being succeeded by GII.3/GII.b recombinant strains, which were a major cause of pediatric disease worldwide from 2000 to 2009 (29,30,33,34,37,54). In contrast, GII.3/GII.a recombinant strains were not as prevalent, causing isolated outbreaks and sporadic disease in Australia, Argentina, and Japan during 1998 and 2002 (55)(56)(57).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A single study conducted in the United States on norovirus strains collected in the 1970s showed that norovirus strains possessing a GII.3 VP1 gene and ancestral RdRp gene were the most prevalent genotype circulating in children at that time (22). Genotype GII.3/GII.3 (capsid/RdRp) noroviruses were prevalent in children globally from the late 1980s to the late 1990s (22,23,26,27) before being succeeded by GII.3/GII.b recombinant strains, which were a major cause of pediatric disease worldwide from 2000 to 2009 (29,30,33,34,37,54). In contrast, GII.3/GII.a recombinant strains were not as prevalent, causing isolated outbreaks and sporadic disease in Australia, Argentina, and Japan during 1998 and 2002 (55)(56)(57).…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant strains have been widely reported in recent years, and a number of novel RdRp genotypes which have no corresponding capsid genotype, such as GII.a and GII.b, have been identified (32). Recombinant strains are frequently detected in children, particularly strains with a GII.3 capsid gene and GII.b RdRp gene (29,31,33,34).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Genotype II.3 (GII.3) is a common cause of sporadic pediatric infections (10)(11)(12)(13), and 70% of children show evidence of GII.3 infection by 2 years of age (14). In sporadic infections in infants and young children, GII.3 strains often predominate, and they were particularly prevalent throughout the late 1970s, late 1980s (10), and early 1990s (15,16) and in the early and late 2000s (13,(17)(18)(19)(20).…”
mentioning
confidence: 99%